MALDI imaging mass spectrometry: molecular snapshots of biochemical systems - Cornett, Dale S; Reyzer, Michelle L; Chaurand, Pierre; Caprioli, Richard M (Nature methods, 2007)
Matrix-assisted laser desorption/ionization ( MALDI ) imaging mass spectrometry (IMS) is emerging as a powerful tool for investigating the distribution of molecules within biological systems through the direct analysis of thin tissue sections. Unique among imaging methods, MALDI -IMS can determine the distribution of hundreds of unknown compounds in a single measurement. We discuss the current state of the art of MALDI -IMS along with some recent applications and technological developments that illustrate not only its current capabilities but also the future potential of the technique to provide a better understanding of the underlying molecular mechanisms of biological processes.